การเปรียบเทียบความสามารถด้านการอ่านภาษาอังกฤษหลังเรียนด้วยนิทาน - ภัทรลดา วงษ์โยธา, รัตนาวดี พรรัมเดช, (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 1 No 2 (2018): ปีที่ 1 ฉบับที่ 2 ประจำเดือนกรกฎาคม - ธันวาคม 2561, 2018)
The purposes of this study were to study and compare English reading comprehension ability using tales of Mattayomsuksa 1 students before and after the instruction, and to study students’ attitude towards teaching English reading comprehension using comprehension using tales. The sample consisted of 33 students of Mattayomsuksa 1 students at Jaturamitwittayakarn school, Khonkaen Province, in the first semester of the academic year 2017. They were selected by purposive selection. The design of this research was a one group pretest-posttest design. The research instruments included 10 lesson plans, an English reading comprehension ability test, and an attitude questionnaire. The findings were as follows; The students’ pretest and posttest mean scores on English reading ability were 8.06 or 40.30 percentand 25.94or 79.70percent respectively. The posttest score was higher than the criteria of 70 percent and it was significantly higher than that of the pretest at the .01 level. 2.The students’ attitude towards teaching English reading comprehension ability using tales was at a good level. Keywords: English reading through fables,reading ability, the students’ attitudes